Tinjauan Yuridis Terhadap Penjatuhan Hukuman dalam Tindak Pidana Penjualan Obat-Obatan Tanpa Izin - Delieshia Marianti; Jopi Jopi; Gogo Lucky Hutagalung (Universitas Medan Area, 2020)
The aim of this research is to review the legal arrangements for drug traffickers without marketing authorization and the Judge's Consideration in imposing the law on perpetrators of Criminal Acts for Drug distribution without marketing authorization in Decision Number: 96 / Pid.SUS/2015/PN.Btl, research using normative juridical methods that are analytical descriptive in nature, Case Approach and Legislation: First, every business people who selling drugs and food in Indonesia must pocket a distribution permit in accordance with the provisions of the applicable laws and regulations in Indonesia, namely the Law Number 36 of 2009 concerning health reads